Acute Pain Management: IV Patient Controlled Analgesia Places the Patient in Control - Maxwell, Lynne (Operating Room Nurses Association of Canada Journal, 1992)
Health care professionals have long been concerned about assessing and treating acute pain. Nonetheless, between one-half and three quarters of post-operative patients experience inadequate pain relief following surgery.“ 9’ 15) Scholars, practitioners and researchers specializing in acute pain encourage health care professionals to examine current practises in the light of new knowledge so that ineffective approaches to acute pain management can be identiﬁed and corrected.